Implementasi Konsep Medan Makna dalam Pembelajaran Holistik Berbasis Deep Learning Guna Mendukung Potensi Diri Siswa SMP Negeri 5 Nekamese - Anastasia J. Leda; Simon Sabon Ola; Aris Nurhuda; Lisky A. Th. Subu Taopan; Yohanes A. Lb. Lamawato (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
SMP Negeri 5 Nekamese, as a remote school, needs to adopt innovative learning practices such as deep learning. The challenge is integrating this abstract concept into classroom practices that support differentiated learning. The solution offered is to combine deep learning with the concept of fields of meaning from linguistics, which helps teachers create contextual materials and facilitates students in building holistic understanding. The Community Service Program (PKM) was implemented through four systematic stages: preparation, training and capacity building for teachers on fields of meaning and deep learning, implementation of modules in the classroom with regular mentoring, and holistic evaluation. The main focus was collaboration between teachers and the community service team in developing teaching modules that support differentiation. This activity successfully produced an innovative teaching module that applies deep learning through the concept of fields of meaning. This module created a paradigm shift from memorization to substantive understanding, strengthening students' contextual understanding and literacy. This success increased teacher capacity and became a replicable asset. This PkM also strengthens Undana's Tri Dharma (Three Pillars of Excellence); lecturers receive theoretical validation and enrich the curriculum, while students gain real-world experience (experiential learning) and strengthen their soft and hard skills. This PkM successfully integrates modern semantics and pedagogy, resulting in improved learning quality in schools. For sustainability, it is recommended that schools institutionalize the teaching modules, and Undana publishes this training model as a case study.